The protection of intellectual property rights in outer space activities - Tosaporn, Leepuengtham (Edward Elgar Publishing, 2017)
While outer space itself remains out of reach for most of us, the results of space activities and developments from space technology are becoming increasingly integrated in our daily lives. Recognising the importance of these technologies, this book explores how existing legal protection methods may be enforced if the unauthorised use takes place beyond conventional territorial borders in outer space. In this detailed and considered study, Tosaporn Leepuengtham examines the problems which may arise in terms of the protection of intellectual property rights in space activities under two national jurisdictions; the US and the UK. She explores the conflict between intellectual property law's scheme of private exclusive rights and the fundamental principle of space law, which is the common heritage of mankind. Furthermore, this book offers potential solutions to this conflict, including suggestions for best practice implementation of law and policy recommendations for balancing and better protecting the interest of rights holders and the public in space activities. Raising pertinent questions, it eloquently provides a springboard for future study. Novel and engaging, this book will appeal to scholars and students of intellectual property law and various related topics including patent and copyright law, space law, private international law and technology law. Government agencies, policy makers and officials, in particular those responsible for issuing and implementing law, regulations and policies governing space industry, will also find a wealth of knowledge herein.